Pemanfaatan Liposom Cerdas Berbasis Nanoteknologi: Terobosan Strategis dalam Pengobatan Tertarget pada Kanker : Smart Liposomes via Nanotechnology: A Breakthrough in Cancer Management Targeted Cancer Therapy - Benni Iskandar; Dina Nurmala Sari; Faura Desi Anggraini; M. Fauzan Prakoso; M. Hafidz Adi Nugraha; Nesya Ananda Triana Putri; Nur Raudha; R. Fikra Nadya Salsabilla; Salsabila Lailani; Tarisha Nadira; Darmawi Darmawi (JURNAL FARMASI DAN MAKANAN, 2025)
The use of nanotechnology in pharmaceuticals, especially for cancer therapy, has shown significant development through the innovation of liposome-based drug delivery systems. Liposomes as delivery nanosystems improve stability, bioavailability, and drug specificity to target cells, while lowering systemic toxicity. Various strategic approaches such as conjugation with antibodies (trastuzumab), enzyme (hyaluronidase), RNA, and combination with siRNA and gold nanoparticles demonstrate remarkable ability to penetrate biological barriers and overcome drug resistance. In addition, multifunctional liposomes allow simultaneous delivery of chemotherapy and immunotherapy synergistically. Based on the results of our literature/review study, it shows that nanotechnology-based liposomes significantly increase the effectiveness of cancer therapy by increasing stability, bioavailability, and drug specificity, and addressing resistance through various strategies such as conjugation and delivery of combinations of therapies. As shown in pancreatic, lung, cervical, and HER2-positive breast cancer therapy. These studies have confirmed that nanotechnology-based liposome formulations are not just a delivery device, but a precision, effective, and potentially changing the paradigm of cancer treatment.